Preparation of DNA/Gold Nanoparticle Encapsulated in Calcium Phosphate - Ito, Tomoko (Hindawi Publishing Corporation, 2011)
Biocompatible DNA/gold nanoparticle complex with a protective calcium phosphate (CaP) coating was prepared by incubating DNA/gold nanoparticle complex coated by hyaluronic acid in SBF (simulated body fluid) with a Ca concentration above 2 mM. The CaP-coated DNA complex was revealed to have high compatibility with cells and resistance against enzymatic degradation. By immersion in acetate buffer (pH 4.5), the CaP capsule released the contained DNA complex. This CaP capsule including a DNA complex is promising as a sustained-release system of DNA complexes for gene therapy.